SENSORY MARKETING: AN EXPERIENCE THROUGH THE SENSES AT NEUROLAB FADE - ESPOCH - Guambo Ramírez, Mariela Mishella; Vasco Vasco, Jorge Antonio; Granizo Espinoza, Ximena Patricia (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
Sensory marketing is used to persuade the emotional part in people, generating emotions, sensations and creating an experience. The objective of the research was to determine the perception that visitors have in the Laboratory of Neuromarketing at the Polytechnic School of Chimborazo. The methodology used is Descriptive, it was carried out in the same study site, in addition a biometric equipment called electroencephalogram was used that measures the level of attention and meditation of people before a stimulus. There is a high percentage of satisfaction level within the laboratory facilities, which was analyzed from a global approach to the activation of the senses through experience so that it can influence the student in a positive way by persuading the limbic part of the brain and generate a long-term memory in the hippocampus. In olfactory aspects, the result of the electroencephalogram determined that the smell of vanilla reduces stress levels and has a greater proportion of attention by the visitor. Developing a sensory environment will contribute positively to guests because it focuses on their well-being, achieving a high level of relaxation for the acquisition of knowledge.